2014
DOI: 10.1371/journal.pone.0103328
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Multidrug-Resistant Tuberculosis Treatment Commencement Times in MDRTBPlus Line Probe Assay and Xpert® MTB/RIF-Based Algorithms in a Routine Operational Setting in Cape Town

Abstract: BackgroundXpert MTB/RIF was introduced as a screening test for all presumptive tuberculosis cases in primary health services in Cape Town, South Africa.Study AimTo compare multidrug-resistant tuberculosis (MDR-TB) treatment commencement times in MDRTBPlus Line Probe Assay and Xpert MTB/RIF-based algorithms in a routine operational setting.MethodsThe study was undertaken in 10 of 29 high tuberculosis burden primary health facilities, selected through stratified random sampling. An observational study was undert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
75
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 17 publications
12
75
1
Order By: Relevance
“…Molecular-based tests, however, can produce results in Ͻ1 day (5,(8)(9)(10)(11)(12). The WHO has endorsed line probe hybridization and molecular beacon assays for the detection of drug resistance in highincidence settings (13).…”
mentioning
confidence: 99%
“…Molecular-based tests, however, can produce results in Ͻ1 day (5,(8)(9)(10)(11)(12). The WHO has endorsed line probe hybridization and molecular beacon assays for the detection of drug resistance in highincidence settings (13).…”
mentioning
confidence: 99%
“…Studies of adults have reported shortcomings and delays in health systems and diagnostic pathways that affect the impact of Xpert on timely treatment initiation and patient outcomes. [32][33][34] Costs for health systems, as well as for patients, have to be taken into account during consideration of the use of a new diagnostic, but no data were provided in the studies included. Additional data are needed to improve use of Xpert (panel).…”
Section: Discussionmentioning
confidence: 99%
“…Among the MDR-TB patients started on treatment, the median time to initiation of treatment was high, at 79 days (n = 5). In the Delhi, India, study 10 (a setting with LPA), the median time to initiate treatment was 37 days, and in South Africa, 14 a setting where Xpert ® MTB/RIF (Cepheid, Sunnyvale, CA, USA) is available, it was 17 days. The delay in our study is unacceptable, and steps are urgently needed to ensure the early initiation of treatment and break the chain of transmission.…”
Section: Public Health Action Mdr-tb Screening In India 137mentioning
confidence: 99%
“…tive models for tracking, including the use of mobile phone reminders 14 and electronic patient registers. 15 2 Health system strengthening: this would include training and re-sensitising the staff of the general health care delivery system, especially DMC laboratory technicians, and developing a mechanism for sputum transport from the DMC to the IRL.…”
Section: Public Health Action Mdr-tb Screening In India 138mentioning
confidence: 99%